An Analyze Working Morale of Occupation Interest in Teaching Profession (Descriptive Anlytical Study of Teachers SDN Bukit Raya Pekanbaru) - arlizon, Raja; saam, Zulfan; Donal, Donal (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The background of the problem in this study are as follows: a) How is the morale and interest in the profession Teacher, b) How is the interest in the position of teachers and teachers morale based on gender in the profession, c) Is there a difference morale and interest in the position of men to women, d) Is there a difference morale and interest in the position of civil servants and non-civil, e) How much the relationship and the contribution of interest in teaching profession on morale. This study used a quantitative approach to the correlation method and comparative. Population in this study was teachersans used total sampling. Data analysis techniques used SPSS (Statistical Product and Service Solution) for windows release 16.0. The findings and the following results: a) Overview morale and interest in the teaching profession was very good category and good, b) Overview interest in the position of teachers based on male was fair category and female good category, c) Overview morale of teachers by male was good category and female very good category, d) There are differences in teachers morale and interest in the position based on the gender, e) There are differences in teachers morale and interest in the position based on the employment status of state civil servants and non-civil servants, f) There is a relationship and influence significant interest in the teaching profession with the morale of teachers.